Feminismo, maternidad y delito : el Derecho Penal y el imperativo de maternidad de las mujeres : el caso de los delitos de omisión - Manelli, Matías (2018)
This paper proposes a debate about how the criminal law and the judicial practices tend to reinforce women's maternal role, rewarding the "good mothers" and punishing, on the other side, any practice contrary to the stereotype configured in the patriarchal discursive matrix, taking by case the crime of "abandonment of person".